(untitled) (AYUSHDHARA, 2017)
Diabetes Mellitus (DM) comprises a group of common metabolic disorder that share the phenotype of hyperglycemia. The Worldwide prevalence of DM has risen dramatically over the past two decades. Based on current trends, more than 360 million individuals will have DM by the year 2030. Prevalence of type II DM is increasing worldwide much more rapidly than type I DM because of increasing obesity and reduced activity level and sedentary lifestyles. Six of the top ten countries with the highest rates of DM are in Asia and India is becoming capital of DM. Diabetes Mellitus can be co-related with Madhumeha dealt in Ayurveda classics. It is a type of Vataj Prameha. In Brihatrayee and Laghutrayee various drugs are described for the treatment of Prameha. Bhavaprakash Nighantu is the clinically important among Laghutrayee; also dealt with various drugs useful for Prameha. Purpose: The purpose of this study is to enlist the herbs useful in DM from Bhavaprakash Nighantu and critically analyze according to the studies done upon them. Material and Methods: Along with Bhavprakash Nighantu other suitable Ayurvedic literatures, contemporary literatures, journals & internet media were also used for collecting information regarding the topic. Result and Discussion: Among 426 Dravyas dealt in Bhavaprakash Nighantu, 47 Dravyas (Herbs) are described as Pramehahara. Besides Takra, Tushar jala, Jangala Mamsa, 3 types of Madhu and 11 Pramehahar Dravyas are described in Dhatwadi Varga. Various studies have proven the efficacy of herbal medicines in treatment of DM.